In Spite of the Chemist's Belief: Metastable Hydrates of CsCl - Závacká, Kamila; Vetráková, Ľubica; Bachler, Johannes; Neděla, Vilém; Loerting, Thomas (ACS physical chemistry Au, 2025)
In this work, we focus on the low-temperature behavior of concentrated aqueous solutions of cesium chloride and discover two hydrates of CsCl. We employ four different methods, namely, (i) simple cooling at rates between 0.5 and 80 K s-1, (ii) simple cooling followed by pressurization, (iii) hyperquenching at 106 to 107 K s-1, and (iv) hyperquenching followed by pressurization. Depending on the method, different types of phase behaviors are observed, which encompass crystallization involving freeze-concentration, pressure-induced amorphization, full vitrification, and polyamorphic transformation. The CsCl hydrates discovered in our work cold-crystallize above 150 K upon heating after ultrafast vitrification (routes iii and iv) and show melting temperatures below the eutectic temperature of 251 K. We determine the composition of these hydrates to be CsCl·5H2O and CsCl·6H2O and find evidence for their existence in ESEM, calorimetry, and X-ray diffraction. The dominant and less metastable hydrate is the hexahydrate, where the pentahydrate appears as a minority species. We also reveal the birthplace for the CsCl hydrates, namely, the freeze-concentrated solution (FCS) formed upon cold-crystallization of the fully glassy solution (from iii and iv). The spongy FCS produced upon cooling of the liquid (from i and ii) is incapable of crystallizing CsCl-hydrates. By contrast, the FCS produced upon heating the glassy solution (from iii and iv) shows tiny, fine features that are capable of crystallizing CsCl-hydrates. Our findings contradict the current knowledge that alkali chlorides only have hydrates for the smaller cations Li+ and Na+, but not for the larger cations K+, Rb+, and Cs+ and pave the way for future determination of CsCl-hydrate crystal structures. The pathway to metastable crystalline materials outlined here might be more generally applicable and found in nature, e.g., in comets or on interstellar dust grains, when glassy aqueous solutions crystallize upon heating.